Credit Policy and Loan Recovery Among SACCOs In Kabale Municipality: A Case Study of Lyamujungu SACCO Kabale Municipality. - Atuheire, Dickson (Kabale University, 2024)
The study assessed the effect of credit management policy on loan recovery in microfinance institutions in Uganda. A case study of Lyamujugu Sacco in Kabale Municipality. The study was guided by three objectives which were: to establish credit management policies applied by Unique Sacco Kabale municipality, to determine the rate of loan recovery at Lyamujugu Sacco Kabale municipality, to establish the relationship between credit management policy and loan recovery at Lyamujugu Sacco Kabale municipality. A targeted population of 50 respondents was considered for the study. These included top management, cashiers, loan officers, clients, and accountants. Both simple random and purposive sampling techniques were used in identifying the study sample size. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. Based on results from the study, 100% of the respondents agreed that there are various credit management policies applied by unique Sacco and these include credit terms that involve both the length of credit period and discount rate, the loan amount recommended by the credit officer, and collateral security. The study findings revealed the rate of loan recovery in microfinance institutions in Uganda's profitability ratio, efficiency ratios, outstanding loans, and real annual average growth rate of loans. From objective three, it was found out as indicated by the respondents from Unique Sacco that there is a relationship between customer credit management policies and loan recovery and these are good credit management provide the institution with reasonable and adequate returns on loans, borrowers are given a small amount of money. The researcher concluded that there are various credit management policies applied at Lyamujugu Sacco. The majority of the respondents reported credit terms involve both the length of the credit period and the discount rate given, offering a uniform interest rate. The study findings further recommend that Unique Sacco should redesign its credit policy so as to make credit management more effective to reduce loan losses and write-offs.